Site‐Resolved Backbone and Side‐Chain Intermediate Dynamics in a Carbohydrate‐Binding Module Protein Studied by Magic‐Angle Spinning NMR Spectroscopy. Issue 30 (12th June 2015) - Ivanir‐Dabora, Hadar; Nimerovsky, Evgeny; Madhu, P. K.; Goldbourt, Amir
Abstract Magic‐angle spinning solid‐state NMR spectroscopy has been applied to study the dynamics of CBM3b–Cbh9A from Clostridium thermocellum (ctCBM3b), a cellulose binding module protein. This 146‐residue protein has a nine‐stranded β‐sandwich fold, in which 35 % of the residues are in the β‐sheet and the remainder are composed of loops and turns. Dynamically averaged 1H‐13C dipolar coupling order parameters were extracted in a site‐specific manner by using a pseudo‐three‐dimensional constant‐time recoupled separated‐local‐field experiment (dipolar‐chemical shift correlation experiment; DIPSHIFT). The backbone‐Cα and Cβ order parameters indicate that the majority of the protein, including turns, is rigid despite having a high content of loops; this suggests that restricted motions of the turns stabilize the loops and create a rigid structure. Water molecules, located in the crystalline interface between protein units, induce an increased dynamics of the interface residues thereby lubricating crystal water‐mediated contacts, whereas other crystal contacts remain rigid.